Econometric Modelling of Energy & Financial Markets - Lips, Johannes; Justus Liebig University Giessen (My University, 2019)
This dissertation consists of two parts with different themes, the first part is made up of three articles in the broad category of empirical energy economics. The first paper in this category analyses the impact of changes in the prices of fossil fuels on the electricity prices. The following two articles are closely related and empirically analyse the North American oil industry to see if the financial decisions and conditions of the firms and the oil industry are affected by oil price changes. The final article provides a literature review prepared for the handbook "Corruption and Fraud in Financial Markets: Malpractice, Misconduct and Manipulation. with an accompanying data analysis on the detection of financial fraud and manipulations using Benford s law.
Ökonometrische Modellierung von Energie- und Finanzmärkten
Keywords: Energieökonomik; Ökonometrie; Statistik; Datenanalyse; energy economics; econometrics; statistics; data analysis; ddc:330